Integration Processes in the asia-Pacific Region with the Participation of China and the Position of Russia - A. V. Kuznetsov (Финансы: теория и практика, 2018)
Flourishing of the East Asian Tigers has led to unparalleled growth in trade in the Asia-Pacific region (APR). The crises of the multilateral trading system and the need to move to a polycentric model of the world order have become the pivotal motives to enhance cooperation in the Asia-Pacific region. Expected to be signed by the end of 2018, a Regional Comprehensive Economic Partnership (RCEP) agreement can be the institutional framework for integration processes in the Asia Pacific region. The Asia-Pacific region is one of the most prospective regions in the world in terms of consuming natural gas and oil. Successful integration processes in Asia depend significantly on the foreign policy priorities of Russia, the key geopolitical player and energy producer. The objective of the article is to reveal the nature of China’s participation in building a new global economy model on the example of the RCEP as well as the position of Russia regarding the integration processes in the Asia-Pacific region. The methods of scientific abstraction, comparative analysis and logical generalization have been used. The main theoretical approaches have been systematized and summarized the analysis of the role of China in the integration processes in the Asia-Pacific region in the context of the polycyclic transformations of the global economy dominant paradigm. China regards the uSA as its main competitor and the usurper of global resources. In recent decades, China has demonstrated undeniable economic achievements based on the success of the industrial policy. China is leading the creation of the world largest trade bloc to be able to determine independently the future agenda of the global economy. However, with no political support, intellectual and raw materials resources of Russia, it will be difficult for China to achieve parity with the West in the world economic arena. It has been concluded that in order to take advantage of the integration processes in the APR, Russia should take an active position in a constructive dialogue with China and other Asia-Pacific countries on numerous unresolved issues of bilateral and multilateral cooperation. Asian investors and consumers should be admitted to Russian oil and gas resources simultaneously with the introduction of Russia in the regional value chain in the Asia-Pacific region on mutually beneficial terms.